1998
DOI: 10.1097/00007632-199802010-00017
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Lumbar Proprioception in Individuals With and Without Low Back Pain

Abstract: Differences in proprioception do exist between individuals with back pain and those free from back pain. Further research needs to be undertaken on proprioceptive exercise programs and their effect on back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
183
3
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(202 citation statements)
references
References 31 publications
6
183
3
7
Order By: Relevance
“…There are receptors responsible for this information which could be affected by dysfunction in the lumbar spine [7]. Accordingly, subjects with LBP may have altered postural control and balance deficits as well as reduced proprioception in the spine, which have been reported in several studies [2,3,7,8].…”
Section: Introductionmentioning
confidence: 94%
“…There are receptors responsible for this information which could be affected by dysfunction in the lumbar spine [7]. Accordingly, subjects with LBP may have altered postural control and balance deficits as well as reduced proprioception in the spine, which have been reported in several studies [2,3,7,8].…”
Section: Introductionmentioning
confidence: 94%
“…4,9,10 Low back disorders have also been associated with changes in trunk reposition sense. 7,11,19 Spinal reposition sense is influenced by many factors such as motion, trunk position, and loading. 1,18 It remains unclear how position sense may be altered in flexion and twisting tasks traditionally associated with LBD risk.…”
mentioning
confidence: 99%
“…Previous studies support the idea that older adults with LBP have reduced proprioceptive sensation on position-reposition accuracy and have a higher prevalence of balance deficits [30][31][32]. Several other studies focusing on typical movement patterns in older adults with LBP identified increased postural sway and decreased lumbar spine motion [33,34].…”
Section: Postural Deficits and Integrated Balance Performancementioning
confidence: 75%